Principles of Three-Dimensional Computer Design for Understanding Impossible Figures - Dovramadjiev, Tihomir (International Journal of Engineering and Management Sciences, 2020)
For a better understanding of the impossible figures, it is advisable to use modern technological means by which the design of the geometry of the models gives a complete understanding of how they are made. Computer-aided 3D design completely solves this problem. That is, on the one hand, the ultimate visual variant of impossible figures is created, on the other hand, there is the possibility for real manipulation, movement, rotation and other models of space. In this study, 3D models of impossible figures are fully constructed, which are applied in the educational process in order to develop logical thinking. The steps of creating 3D geometry using open source software Blender 3D are described in details.